Pengembangan Modul Pembelajaran PKN berbasis Kearifan Lokal Siswa Sekolah Dasar - Nurulanifah; Nurdin Kaso; Edhy Rustan (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This review examines the improvement of Civics learning modules regarding the matter of ethnic and social variety in view of nearby insight in 4th-grade understudies at SDN 178 Tuban, Tomoni District, East Luwu Regency. This review intends to decide the requirement for learning modules for ethnic and social variety in view of neighborhood astuteness for 4th-grade understudies at SDN 178 Tuban, Tomoni District, East Luwu Regency, to decide the plan of learning modules for ethnic and cultural diversity based on local wisdom for fourth-grade students at SDN 178. Tuban, Tomoni District, East Luwu Regency and to determine the validity of the learning module for ethnic and cultural diversity based on local wisdom for fourth-grade students at SDN 178 Tuban, Tomoni District, East Luwu Regency. This type of research is Research and Development (R&D). To produce Civics learning module products, the researcher refers to the BANATHY model with seven steps, namely initial research and initial information collection, planning, developing an initial product form, initial product testing, revision of test results, expert validity and product test results. The research was conducted at SD Negeri 178 Tuban, Tomoni District, East Luwu Regency with the research subjects being fourth-grade students totaling 27 students consisting of 15 female students and 12 male students, while the object of the research focused on developing Civics learning modules for ethnic and cultural diversity. . After the product was developed, the researcher distributed a validation questionnaire to the validator team to determine the feasibility of the product being developed. The validators consist of material expert validators, media experts, and linguists. The results from the validation of the material experts that have been analyzed get a percentage (84%), the results from the media expert validation get a percentage (78%) and the results from the language validation get a percentage (81%). From the results of the validator team, it is in the very valid category. Based on these results, it was concluded that the Civics learning module on the subject of ethnic and cultural diversity based on local wisdom in fourth-grade students at SDN 178 Tuban, Tomoni District, East Luwu Regency met the validity criteria with a very valid category and the product was ready to be used in the learning process. teach in class.